MANAJEMEN WAKTU, BIAYA DAN SDM PROYEK KONSTRUKSI PADA PEMBANGUNAN GEDUNG RUANG KULIAH FIA UNIVERSITAS BRAWIJAYA MALANG DENGAN MENGGUNAKAN METODE PERT DAN PDM - Fakhrur Rozy, Anugerah; R.G.W., Ode (Media Teknik Sipil, 2014)
MANAJEMEN WAKTU, BIAYA DAN SDM PROYEK KONSTRUKSIPADA PEMBANGUNAN GEDUNG RUANG KULIAH FIAUNIVERSITAS BRAWIJAYA MALANGDENGAN MENGGUNAKAN METODE PERT DAN PDMAnugerah Fakhrur Rozy1, Ode R.G.W.21,2Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144ABSTRACProject managers always want to find a method which can improve quality and control to dealwith the number of activities that tend to increase. To improve the quality of planning and control ofthe building project B FIA UB used a method, and the method used herein is Project Evaluation andReview Technique (PERT) Method and Presedence Diagram Method (PDM) with a software programtool Microsoft Office Project 2003.Completion time planning the optimal project using PERT and PDM is 303 days with atotal cost Rp 16,278,036,000.00 (including contractors profit + 10% PPN). From the calculation ofthe target analyte project completion time T (d), shows that the possibility of the project is completedon time / period of 303 days (normal time) only by 50%. Whereas if the duration / Project Completionperiod plus 3S (three times the standard deviation) is 303 days + 14.13 = 317.13 days, then it islikely the project is completed on time / period of 317.13 days at 99% (on time).Keywords: Time, Cost, SDM, PERT Method, PDM, Microsoft Office Project 2003.